ANALISIS PERSEPSI MANAJEMEN KSPPS TERHADAP KEMUNGKINAN PENERAPAN PROFIT EQUALIZATION RESERVE BERSARKAN FATWA DSN-MUI - Abdul Muis; M. Nasyah Agus Saputra; Moh. Ya’qub (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, IAIN Fattahul Muluk Papua, 2026)
Fluctuations in profit-sharing rates on mudharabah-based term deposit products may result in unstable returns and increase the risk of displaced commercial risk in Islamic financial institutions. One mechanism designed to stabilize profit distribution is the Profit Equalization Reserve (PER), as stipulated in the DSN-MUI Fatwa No. 87/DSN-MUI/XII/2012. However, the implementation of PER in Indonesian Islamic cooperatives remains limited. This study aims to analyze the management's perception of the potential implementation of PER in the term deposit products of KSPPS Mitra Usaha Ideal Sidayu and to examine its compliance with DSN-MUI Fatwa No. 87/DSN-MUI/XII/2012. A qualitative approach with a case study design was employed. Data were collected through semi-structured interviews, observations, and documentation involving cooperative board members, the head of finance, the head of marketing, and relevant staff. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña through data reduction, data display, and conclusion drawing. The findings indicate that KSPPS Mitra Usaha Ideal Sidayu has not implemented PER due to the absence of adequate internal policies, operational procedures, and governance mechanisms. The study further reveals that the principal obstacle to PER implementation is not Sharia compliance but institutional readiness. Nevertheless, management perceives PER as an effective instrument for stabilizing profit-sharing rates, strengthening members' trust, and enhancing the cooperative's competitiveness. Furthermore, members' loyalty is influenced more by service quality and institutional trust than by fluctuations in profit-sharing rates. Therefore, strengthening internal regulations, governance, and operational systems is a fundamental prerequisite for the successful implementation of PER in Islamic cooperatives.